Transforming user’s experience on streaming TV: innovation and technology priorities for OTT platforms - Fieiras Ceide, César; Ufarte Ruiz, María José; Murcia Verdú, Francisco José (Estudios sobre el Mensaje Periodístico, 2024)
This research analyses the priorities and innovation strategies of the 10 OTT service operators with the largest share of consumption in Spain, to identify trends in optimising the user experience, viewing modalities, and personalised content production and distribution. To do so, we examined the corporate communications, reports and platforms of these companies and held 9 interviews with professionals in senior management positions at Netflix, Movistar Plus+, HBO Max, Vodafone TV, Orange TV, DAZN and AtresPlayer. These companies base their strategies on prototypes based on artificial intelligence (AI), extended reality (XR), or 360 technologies, with which they seek to personalise services, offer immersive experiences, optimise the usability of the systems, as well as enable shared consumption between remote users, achieve a liquid experience between media and maximise distribution on the greatest number of devices, all to reinvent the user experience, considered as a priority and differential value. In the technical field, OTT operators are introducing concepts such as remote production, productions with virtual sets, virtual interviews, the integration of “Unreal Engine” (Epic Games) or the integration of 3D models in corporeal sets. They also plan to incorporate projects that involve volumetric video capture, virtualized remote production in the cloud or automatic production using AI.
Keywords: innovation; broadcasting; video on demand (VoD); streaming; user experience